Salicylic acid induced the expression of phenylalanine ammonia-lyase gene in grape berry - Wen, P.; Chen, J.; Kong, W.; Pan, Q.; Wan, S.; Huang, W.
Many evidences had indicated that both salicylic acid (SA), a likely signal in resistance responses of plants to stresses, and phenylalanine ammonia-lyase (PAL; EC 4.3.1.5), a key enzyme in the phenylpropanoid pathway, could perform defense-related functions. However, whether to regulate PAL activity by SA has been to date obscure. The present experiment, using the technique of in vivo incubation of the grape berry (Vitis vinifera L. cv. Cabernet Sauvignon)tissue in the SA-contained medium, showed that SA could induce the accumulation of PAL mRNA and the synthesis of new PAL protein, and increase the activity. The activation of PAL by SA could e blocked by the pretreatments of berry tissues with the protein synthesis inhibitor cycloheximide, mRNA transcription inhibitor actinomycin D and PAL inhibitor 2-amino-2-indanophonic acid (AIP), respectively. These results suggest that the development of acquired resistance by SA previously reported may be attributed, at least partly, to the SA-induced PAL gene expression and activation.
Keywords: GRAPE BERRY; PHENYLALANINE AMMONIA-LYASE; SALICYLIC ACID; GENE EXPRESSION; WESTERN BLOT; RT-PCR